2020
DOI: 10.1038/s41416-020-0741-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined lifestyle factors, incident cancer, and cancer mortality: a systematic review and meta-analysis of prospective cohort studies

Abstract: Background Cancer poses a huge disease burden, which could be reduced by adopting healthy lifestyles mainly composed of healthy diet, body weight, physical activity, limited alcohol consumption, and avoidance of smoking. However, no systematic review has summarised the relations of combined lifestyle factors with cancer morbidity and mortality. Methods EMBASE and PubMed were searched up to April 2019. Cohort studies investigating the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 40 publications
(23 reference statements)
6
131
2
Order By: Relevance
“…Some of our analyses did not have enough power to detect significant results. Especially, our null finding for cancer mortality, which is contrary to previous studies that showed an inverse association between healthy lifestyles and cancer mortality 36 , can be due to limited follow-up time and number of cancer deaths, or by chance and thus should be interpreted with caution. More prospective studies with longer follow-up period are needed to reexamine cause-specific mortality in this population.…”
Section: Discussioncontrasting
confidence: 99%
“…Some of our analyses did not have enough power to detect significant results. Especially, our null finding for cancer mortality, which is contrary to previous studies that showed an inverse association between healthy lifestyles and cancer mortality 36 , can be due to limited follow-up time and number of cancer deaths, or by chance and thus should be interpreted with caution. More prospective studies with longer follow-up period are needed to reexamine cause-specific mortality in this population.…”
Section: Discussioncontrasting
confidence: 99%
“…Factors such as more aggressive treatment regimens in younger patients and lifestyle choices, before and after an early diagnosis of lung cancer, may influence survival. 32,33 Life expectancy is affected by smoking patterns in the general population, and tobacco smoking is one of the most important risk factors of disease burden and mortality. [34][35][36] In the present cohort, women more often were never smokers, whereas men were more likely to be former smokers, which is in accord with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as more aggressive treatment regimens in younger patients and lifestyle choices, before and after an early diagnosis of lung cancer, may influence survival. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the healthy lifestyle score was the sum of the points and ranged between 0 and 4, with higher scores indicating healthier lifestyles. Although this simple additive method has been used widely,303132 the underlying assumption is that the associations between different lifestyle factors and the outcome were identical, which might not be true. Thus we also constructed a weighted lifestyle score, where each lifestyle factor was weighted by its association with the outcome.…”
Section: Methodsmentioning
confidence: 99%